A case study on ground reaction forces in sprint hurdles - Shibayama, K.; Fujii, N.; Takenaka, S.; Tanigawa, S.; Ae, M. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The purpose of this case study was to investigate characteristics of ground reaction forces in sprint hurdles. Four male Japanese hurdlers participated in this study. The 1-cycle motions from 5th to 6th hurdles were videotaped with two high-speed cameras (300Hz) and ground reaction forces were measured (1000Hz). The hurdler who had smaller horizontal velocity of CG during hurdling had large braking time, which increases impulses of both horizontal and vertical components at 1st step. Therefore, maintaining large horizontal velocity during hurdling seems to be one of the important factors in sprint hurdles.